Refinement influence in the cleaning efficacy of rotary nickel-titanium Mtwo ® instruments in oval-shaped canals by means of optical microscopy - Cibella Maymone Pontes; Luciana Moura Sassone; Cristiana Francescutti Murad; Rivail Antônio Sérgio Fidel; Fernando Sili Vilhena (Wolters Kluwer Medknow Publications, 2014)
Objective: This study evaluated the cleaning efficacy of the rotary nickel-titanium Mtwo ® by means of optical microscopy in oval-shaped root canals and compared refinement influence using ultrasonic files or Hedströem files. Materials and Methods: Twenty mandibular incisors were accessed, included in epoxy resin blocks, and cut transversely at 3, 6, and 9 mm from the apex. Teeth were instrumented using rotary nickel-titanium Mtwo. Digital images of the root cross sections were obtained before and after instrumentation with a digital camera attached to an optical microscope. Subsequently, samples were randomly divided into two groups for refinement. Group I was refined using ultrasonic files #30 and group II with Hedströem files #30. Final digital images of cross sections after refinement were captured and analyzed. The boundaries for the uninstrumented perimeter were measured by the software ImageTool 3.0. The data obtained were statistically analyzed by analysis of variance (ANOVA) and t-test. Results: Mtwo instrumentation produced 41.48% of the uninstrumented perimeter. The final refinement using Hedströem and ultrasonic files decreased the uninstrumented perimeter. Significant differences (t-test, P = 0.00) were found at the three thirds after the final refinement, except for the apical third that was enhanced by Hedströem file. However, there was no statistical difference between the two refinement techniques used (P > 0.05). Mtwo instrumentation was not capable of cleaning and shaping the entire perimeter of the root canals walls. Conclusions: The final refinement, either with ultrasonic files or with Hedströem files, resulted in significantly less uninstrumented perimeter.